Residents' participation in rural tourism and interpersonal trust in tourists: The mediating role of residents’ perceptions of tourism impacts - Huo, Tingting; Yuan, Feng; Huo, Mingmin; Shao, Yuhong; Li, Sijin; Li, Zhiyong (Journal of hospitality and tourism management, 2023)
Interpersonal trust is a critical psychological factor that reveals the quality of resident-tourist relationship in tourism destinations. However, residents' positive attitudes toward tourists are gradually taken for granted, with research on residents' psychological tendency (i.e., interpersonal trust) in providing tourism services and creating mutually beneficial resident-tourist interaction lagging behind. Based on interpersonal relationship theory and social exchange theory, this study employed a sequential mixed-methods design to examine the formation of interpersonal trust in tourists during resident participation in rural tourism. The dimensions of resident participation (i.e., decision-making, economic, and social participation) and the conceptual model were first identified through qualitative analysis. Subsequently, through the PLS-based structural equation modeling using a sample of 469 residents from Jiuzhai Valley, China, the study suggested that economic and social participation were instrumental in shaping residents' cognitive and affective trust in tourists both directly and indirectly through residents’ perceived benefits of tourism. This study offers implications for academia and destination management to promote sustainable tourism development and social harmony against the crisis of trust between residents and tourists caused by the COVID-19 pandemic.